Conceptualising a policy framework for the implementation of medical marijuana in the Caribbean territory of Barbados. (August 2018) - Griffith, Alana DD; Cohall, Damian H
Unlike the recent global trend of a decline in the prohibition of the use of Cannabis sativa for recreational and medical uses, Barbados and other small island states in the Caribbean have maintained their prohibitive legislation and policies on the use of the herb. A negative social construct of the use of cannabis and its effects in the consciousness of many in the Caribbean have contributed to the maintenance of the prohibitive policies towards the use of the herb. This article highlights the negative societal construct of the herb and its impact on the youth as two critical factors limiting the implementation of medical marijuana laws. It conceptualises a possible policy framework that would address this issue by enabling a phased implementation of the use of medicinal products from marijuana in the management of selected conditions from an evidence-based vantage point. Barbados would need to evaluate the mechanisms under current prohibitive legislation and create amendments to allow for an incremental approach on the use of the plant or products thereof for medicinal purposes in light of societal concerns. The policy framework should result in discreet enforceable mechanisms to facilitate and monitor the importation and development of efficacious and safe medicinal products for prescribing to authorised patients throughout the island's healthcare system.